2010
DOI: 10.1007/s00429-010-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

The insular cortex: a comparative perspective

Abstract: The human insular cortex is involved in a variety of viscerosensory, visceromotor, and interoceptive functions, and plays a role in complex processes such as emotions, music, and language. Across mammals, the insula has considerable morphologic variability. We review the structure and connectivity of the insula in laboratory animals (mouse, domestic cat, macaque monkey), and we present original data on the morphology and cytoarchitecture of insular cortex in less common species including a large carnivore (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 92 publications
4
94
0
Order By: Relevance
“…In fact, recent studies on cetacean cerebral cortices have revealed a complex cytoarchitecture, comparable to that observed in many mammals, including primates Hof and Van der Gucht 2007;Butti et al 2009;Butti and Hof 2010). The present study examines such neuromorphological diversity by exploring regional variation in neuron morphologies across all layers of the elephant cortex and by examining quantitative differences in superficial (i.e., layers II-III) pyramidal neurons between frontal and occipital cortical regions.…”
Section: Introductionmentioning
confidence: 74%
“…In fact, recent studies on cetacean cerebral cortices have revealed a complex cytoarchitecture, comparable to that observed in many mammals, including primates Hof and Van der Gucht 2007;Butti et al 2009;Butti and Hof 2010). The present study examines such neuromorphological diversity by exploring regional variation in neuron morphologies across all layers of the elephant cortex and by examining quantitative differences in superficial (i.e., layers II-III) pyramidal neurons between frontal and occipital cortical regions.…”
Section: Introductionmentioning
confidence: 74%
“…In concert, it has been suggested that the anterior portion of the human insula may not have an equivalent in the rat or monkey brain ((Bud Craig, 2009), but see (Nieuwenhuys, 2012) for alternate views). Furthermore, citing evidence for substantial variability with respect to extent, shape, gyral and sulcal patterns, and laminar organization of insular cortex, a recent study across several species suggests “it is not possible to identify a general model of organization for the mammalian insular cortex” (Butti & Hof, 2010), although earlier comparative anatomical work suggests substantial overlap between the human insula and that of other hominoids (see (Nieuwenhuys, 2012) for review). These controversies regarding anatomical organization have made functional characterization of the insula in the human brain all the more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The next three articles address neuroanatomical issues that are significant for our appreciation of how special the human insula really is, and these articles underscore fertile opportunities for neurogenetic and functional analyses (Butti and Hof 2010;Allman et al 2010;Kurth et al 2010). The next five articles provide convergent views on the role of the human insula in affective feelings from the body and subjective emotional feelings, and each one presents novel insights on the functional organization of the human insula (Medford and Critchley 2010;Small 2010;Craig 2010;Lamm and Singer 2010;Garavan 2010).…”
mentioning
confidence: 99%